Novel green phosphorescence from pristine ZnO quantum dots: tuning of correlated color temperature. Issue 1 (21st December 2015) - Das, Sagnik; Ghosh, Chandan Kr.; Dey, Rajib; Pal, Mrinal
Abstract : Creating novel functionality is always fascinating as well as advantageous from a device point of view. Abstract : Creating novel functionality is always fascinating as well as advantageous from a device point of view. We have tried with success to generate green phosphorescence, a novel phenomenon, in pristine zinc oxide quantum dots synthesized by alkaline hydrolysis of a methanolic solution of zinc acetate dihydrate. The appearance of phosphorescence with radiative lifetimes of 4–22 μS is attributed to the singly charged oxygen vacancy . The presence of has been confirmed using electron paramagnetic resonance (EPR) and micro-Raman spectroscopy. In addition, optimization of the intensity and lifetime of the phosphorescence has been made by tailoring the number of and their variation has been satisfactorily explained on the basis of a donor–acceptor pair recombination mechanism. Tailoring of the Commission Internationale de I'Eclairage (CIE) coordinates ( x = 0.317, y = 0.544 in case of pristine ZnO quantum dots) of the synthesized quantum dots has been investigated in the presence of . Correlated color temperature of the quantum dots is evaluated and they are found to be suitable in cold light applications.